MOVING TO CIRCULAR ECONOMY FOR CORPORATE SUSTAINABLE DEVELOPMENT - Valeepitakdej, Vipavee; Pinniem, Sawanya; Prasitsaengaree, Surisa; Ruanghiran, Sonthaya (Journal of Social Science and Cultural, 2023)
This academic article aims to propose a guideline for driving corporate circular economy which was studied and synthesized documents and research papers. The paper begins with the blueprint of 17 Sustainable Development Goals (SDGs) addressing the global challenges that mankind is facing. Meanwhile, it indicates how the corporate circular economy is an effective tool for building sustainability and preserving natural resources and environment according to SDGs targets. The paper also explains the differences between the notions of linear economy and the circular economy in reducing environmental impacts. It indicates several strategies for building the circular economy which can be adopted by all companies. However, firms should select strategies appropriately by considering their product life cycles, internal production processes, and organizational contexts and environment. There are 10 R strategies that can be the best fit for firms. The paper provides case studies of circular economy management from prominent organizations. Problems that have hindered the successes of circular economy are mentioned in this article. Those problems come from both internal and external organizations. For the internal factors, most problems are found such as less awareness towards the importance of circular economy, inflexible organizational structure, fault attitude towards circular economy investment, and the problems of business partners. Meanwhile, Laws and regulations, and potential market are external factors impeding the circular economy progress. Finally, the article proposes a guideline for building the corporate circular economy which is composed of six steps as follows: setting the objective and targets, suitably selecting and creating strategies, building awareness for all members of organization, cooperating strategies with business partners, creating marketing communications for customers and seeking incentives programs from government. Those will lead to the successes of managing corporate circular economy.